Akram’s lifestyle: An effective remedy for the management of gastroesophageal reflux disease - Sadia A. Khan; Javeria Z. Khan; Tayyab S. Akhter; Hamama-Tul-Bushra Khaar; Talay Yar; Mohammad A. Randhawa (Journal of Family and Community Medicine)
INTRODUCTION: The prevalence of gastroesophageal reflux disease (GERD) has generally increased worldwide. Irregular pattern of intake of meals are known to be the most prevalent cause of GERD. The intake of food on top of another meal may cause gastroesophageal reflux either by generating transient lower-esophageal sphincter relaxations (TLESRs) subsequent to distention of the upper part of the stomach or/and delayed gastric emptying due to inhibition of migrating motor complexes (MMCs) in the distal part of the stomach. Present study evaluated the effect of authors suggested regimen “Akram’s lifestyle”, taking meals twice-a-day with the liberty to consume only liquids in the intervening periods on the outcome of patients presenting with mild to moderate GERD. MATERIALS AND METHODS: Study included 60 patients with symptoms of GERD who agreed to follow “Akram’s lifestyle”, took two meals a day about 10-12 hours apart, consuming liquids in between meals for a period of two weeks. Typical GERD symptoms of heartburn, acid reflux, nausea, vomiting and dyspepsia as reported by the patients were scored on visual analog scale (VAS). Gastrointestinal and associated complaints were also evaluated by “Yes/No” response. Data obtained before and after two weeks of intervention was analyzed using SPSS version 28.0. RESULTS: Final data after 2 weeks were available for 45 patients. There was a highly significant improvement in GERD symptoms (heartburn, reflux, nausea, vomiting, and dyspepsia) within 2 weeks of dietary intervention (P < 0.000). Improvement was also reflected in the significant reduction (>69%) in the gastrointestinal complaints as evaluated by “Yes/No” responses after the dietary intervention. CONCLUSIONS: Adherence to “Akram’s lifestyle” for GERD for 2 weeks resulted in a significant improvement or complete relief of symptoms of patients with GERD. Reduced gastric acid secretion, TLESRs and enhanced gastric emptying could be the potential contributing factors in causing this improvement. Further investigations with larger samples are needed to confirm the findings.